Health risk assessment of volatile organic compounds (VOCs) in a refinery in the southwest of Iran using SQRA method - Khajeh Hoseini, Ladan; Jalilzadeh Yengejeh, Reza; Mohammadi Rouzbehani, Maryam; Sabzalipour, Sima (Frontiers in Public Health, 2022)
Oil industries, such as oil refineries, are important sources of volatile organic compounds production. These compounds have significant health effects on human health. In the present study, a health risk assessment is carried out on volatile organic compounds (VOCs) in the recovery oil plant (ROP) unit of a refinery in southwest Iran. It was performed using SQRA method including respiratory risk for Chronic daily intake (CDI ) of VOCs and cancer risk and non-cancer risk indices. Five locations in the area of oil effluents and five locations in the refinery area (control samples) were considered for evaluation. The sampling was done according to standard NIOSH-1501and SKC pumps. The gas chromatography/flame ionization detector (GC/FID) method was used to extract VOCs. The cancer slope factor (CSF) and respiratory reference dose (RFC) were calculated in addition to the respiratory risk (CDI). The end result shows that a significant difference was observed between the concentrations of volatile organic compounds in the two grouped air (P<0.05). The SQRA risk assessment showed that the risk levels of benzene for workers in the pit area were very high (4 to 5). Health hazard levels were also evaluated as a high levels for toluene (2 to 4) and moderate levels for xylene and paraxylene (1 to 3). The cancer risk assessment of volatile organic compounds recorded the highest level of cancer risk for benzene in the range of petroleum effluents (>1.). Also, a non-cancer risk (HQ) assessment revealed that benzene had a significant health risk in the range of oil pits (2-3). Based on the results, Petroleum industries, including refineries, should conduct health risk assessment studies of volatile organic compounds. The units which directly related to the high level of VOCs should be considered sensitive groups, and their employees should be under special management to reduce the level of exposure to these compounds and other hazardous compounds.